Current concepts of the crosstalk between lncRNA and E2F1: shedding light on the cancer therapy - Huang, Peng; Wen, Feng; Li, Qiu (Frontiers in Pharmacology, 2024)
Long noncoding RNAs (lncRNAs) constitute a distinctive subset of RNA molecules with limited protein-coding potential, which exert crucial impacts on various biological activities. In the context of cancer, dysregulated lncRNAs function as essential regulators that affect tumor initiation and malignant progression. These lncRNAs serve as competitive endogenous RNAs (ceRNAs) through sponging microRNAs and regulating the expression of targeted genes. Moreover, they also directly bind to RNA-binding proteins, which can be integrated into a complex mechanistic network. E2F1, an extensively studied transcription factor, mediates multiple malignant behaviors by regulating cell cycle progression, tumor metastasis, and therapeutic response. Emerging evidence suggests that lncRNAs play a pivotal role in regulating the E2F1 pathway. This review aims to elucidate the intricate gene regulatory programs between lncRNAs and E2F1 in cancer progression. We elaborate on distinct mechanistic networks involved in cancer progression, emphasizing the potential of the lncRNAs/E2F1 axes as promising targets for cancer therapy. Additionally, we provide novel perspectives on current evidence, limitations, and future directions for targeting lncRNAs in human cancers. Fully deciphering the intricate network of lncRNA/E2F1-mediated regulatory mechanisms in cancer could facilitate the translation of current findings into clinical course, such efforts ultimately significantly improve the clinical prognosis of cancer patients.